Synergistic effect of sertraline and disulfiram against multidrug resistant bacteria as a new alternative to drug repositioning (Brazilian Journal of Pharmaceutical Sciences, 2020)
The repositioning of approved drugs is atopic of interest for the academy and the pharmaceutical industry. The synergistic combination of these drugs can be successful in the treatment of infections caused by resistant bacteria. This study aimed to assess the in vitro synergistic antibacterial activity of sertraline and disulfiram and their interaction with ciprofloxacin and sulfamethoxazole/trimethoprim. We determined the minimum inhibitory concentration, the minimum bactericidal concentration and the fractional inhibitory concentration index. Eighteen bacterial strains were used, being nine American Type Culture Collection reference strains and nine multidrug resistant clinical isolates. Synergy was detected between sertraline and disulfiram against a strain of Staphylococcus aureusATCC 25923 and a clinical isolate of S. aureus. When associated to sulfamethoxazole/trimethoprim and ciprofloxacin, sertraline and disulfiram showed eight synergistic events, which occurred against three different standard strains and two multidrug resistant clinical isolates. When the minimum bactericidal concentration was determined, the bactericidal activity of sertraline was enhanced with disulfiram. Our results suggest that these drugs, widely used to treat depression and chronic alcoholism, have antibacterial potential individually, in association, and combined with antimicrobials, what makes their repositioning a promising therapeutic alternative for the effective treatment of infections caused by multidrug resistant bacteria.